1986
DOI: 10.1007/bf00384788
|View full text |Cite
|
Sign up to set email alerts
|

Abundance of macrofauna in dense seagrass is due to habitat preference, not predation

Abstract: Two main hypotheses compete to explain why prey abundance decreases when seagrass density is reduced. One proposes that predators are more successful amongst seagrass of lower density; the other invokes habitat choice by prey. We reduced the density of seagrass in the presence, and in the absence, of predators in a field experiment to discriminate between these hypotheses. When seagrass was manipulated abundances of all six prey species decreased simultaneously both in the presence and in the absence of predat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
90
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(105 citation statements)
references
References 17 publications
12
90
1
2
Order By: Relevance
“…2). This finding is in accordance with literature indicating the importance of vegetated areas, such as seagrass beds, for settlement and nursery of several species of grouper and snapper (Allen, 1985;Bell & Westoby, 1986;Bell et al, 1987;Bell & Pollard, 1989;Jory & Iversen, 1989;Chester & Thayer, 1990;Heemstra & Randall, 1993;Jenkins et al, 1997;Tolan et al, 1997). A reason for the seagrass preference of juvenile groupers and snappers is the diverse and abundant invertebrate fauna in this habitat, which is supported by the plants.…”
Section: Seagrass As a Nursery And Feeding Habitatsupporting
confidence: 93%
See 1 more Smart Citation
“…2). This finding is in accordance with literature indicating the importance of vegetated areas, such as seagrass beds, for settlement and nursery of several species of grouper and snapper (Allen, 1985;Bell & Westoby, 1986;Bell et al, 1987;Bell & Pollard, 1989;Jory & Iversen, 1989;Chester & Thayer, 1990;Heemstra & Randall, 1993;Jenkins et al, 1997;Tolan et al, 1997). A reason for the seagrass preference of juvenile groupers and snappers is the diverse and abundant invertebrate fauna in this habitat, which is supported by the plants.…”
Section: Seagrass As a Nursery And Feeding Habitatsupporting
confidence: 93%
“…4, 5), which is in accordance with the selection by pelagic larvae of structurally complex microhabitats for their first settlement. Redistribution of juveniles only takes place within the selected seagrass bed, because crossing bare substrate increases the risk of predation (Bell & Westoby, 1986;Bell et al, 1997). Irlandi et al (1995) argue that rates of predation increase with increased fragmentation of the seagrass habitat.…”
Section: Seagrass As a Nursery And Feeding Habitatmentioning
confidence: 99%
“…Bell and Westoby (1986a) found a positive relationship between the density of the meadow and the abundance of small fish in terms of the presence/absence of predators, suggesting that fish are capable of discriminating between more or less dense meadows, or between meadows and adjacent bottoms lacking vegetation. In the present study no relationship was found between structural complexity and the richness and abundance of the associated ichthyofauna; this is probably due to the spatial scale of the study.…”
Section: Diferencias Entre Islas Y Praderasmentioning
confidence: 93%
“…Aunque la distribuci贸n de las comunidades bent贸nicas en el ambiente sea regulada por procesos din谩micos abi贸ticos, donde los organismos presentan afinidades por determinados h谩bitats, la estructura de las mismas es primariamente un reflejo de la complejidad del h谩bitat, donde las interacciones entre los organismos, sobretodo la competencia y la depredaci贸n, pueden estar 铆ntimamente ligadas a el control de la densidad poblacional de la fauna asociada (Bell & Westoby 1986, Preston & Moore 1988. La intervenci贸n antropog茅nica puede promover alteraciones en el modelo esperado de composici贸n y distribuci贸n espacial de los organismos bent贸nicos costeros, sobretodo en regiones portuarias, sujetas a las fuertes agresiones ambientales, provenientes de fuentes de poluci贸n como las cloacas dom茅sticas, hospitalarias e industriales y a la recepci贸n de especies ex贸ticas transportadas por embarcaciones en viajes transoce谩nicos (Farrapeira 2006).…”
Section: Introductionunclassified